(untitled) (Research, Society and Development, 2021)
Currently, the potential uses of essential oils in contexts of areas that have undergone environmental remediation processes are little known. This work aimed to carry out a systematic review on the potential uses of essential oils with application in situations of environmental remediation. The systematic search was carried out in three databases (Web of Science, PubMed and Scielo) using descriptors and Boolean operators (“AND”, “OR”, “NOT”). All selected results were exported from the databases for further analysis in the free software VOSviewer, building the bibliometric networks, bibliometric mapping and graphical representation of the maps. The general visualization map of term co-occurrence networks indicated 7 to 19 clusters with keywords. The essential oils of Eucalyptus, Sicilian Lemon, Lemongrass, Melaleuca, Cloves and Lavender stand out as the most used in the analyzed research. The approaches most focused on environmental remediation were based on the analysis of aromatic plants to remedy environments impacted by metals, highlighting also the use of essential oils in studies with insecticide / pest control (24%), antimicrobial against environmental pathogens (20% ), fungal bioremediation (20%) and phytoremediation in general (17%). Aromatic plants (from the families Poaceae, Lamiaceae, Asteraceae and Geraniaceae) were used in research on remediation of contaminated sites because they act as potential phytostabilizers, hyperaccumulators, bio-monitors and facultative metallophytes. These data indicate the potential of essential oils (and aromatic plants) in environmental remediation processes, indicating their use in situations where there are areas that need to be remedied and require immediate intervention.